Microwave ablation compared with radiofrequency ablation for the treatment of liver cancer: a systematic review and meta-analysis - Spiliotis Antonios E.; Gäbelein Gereon; Holländer Sebastian; Scherber Philipp-Robert; Glanemann Matthias; Patel Bijendra (Radiology and Oncology, 2021)
Guidelines have reported that although microwave ablation (MWA) has potential advantages over radiofrequency ablation (RFA), superiority in efficacy and safety remain unclear. Aim of the study is to compare MWA with RFA in the treatment of liver cancer.